Twinning in Ni–Fe–Ga–Co shape memory alloy: Temperature scaling beyond the Seeger model. (June 2017) - Kustov, S.; Cesari, E.; Liubimova, Iu.; Nikolaev, V.; Salje, E.K.H.
Abstract: The temperature dependence of the macroscopic de-twining stress in Ni–Fe–Ga–Co shape memory alloy is proportional to the temperature dependence of the micro-yield stress. This proportionality holds for all values of the reversible anelastic strain derived from non-linear internal friction experiments and contradicts predictions of the Seeger model for the temperature dependence of the yield stress. The Seeger model requires two length scales which leads to the independence of two yield stress components. Instead, we find the self-affine behaviour of anelastic strain, which excludes all separations of lengthscales. Graphical abstract: Comparison between the temperature dependence of the macroscopic de-twinning stress σ c ( T ) and the micro-yield stress σ ε ( T ), corresponding to a constant value of reversible anelastic strain ε an  = 6 × 10 − 8 in a martensitic Ni49 Fe18 Ga27 Co6 alloy.